Community intervention in urban areas: A youth driven initiative - Carvalho, Cláudia P. (2017)
This paper aims to reflect on the results of the project Community Intervention in Urban Areas: a youth driven initiative. This project envisioned the development of a Transnational Seminar that gave origin to the development of youth arts intervention projects and to the elaboration of the document “Youth Policies for Urban Neighborhoods”. The project started from the youth’s reflection on the physical, social, economic, and cultural degradation of specific spaces/territories and communities in Portugal, Italy, the Netherlands, and Belgium (spaces in ruins, non-places and other abandoned areas), exploring these territories as spaces for transformation and future renovation. The idea is to explore the ways youth may contribute to the transformation of these spaces, therefore enhancing their civic knowledge, capacity to intervene and influence policy and research under this theme. We wish to explore the role of younger generations, and youth in particular, through a change of paradigm. That is, by developing alternatives of intervention, through Participant Action Research and through the exploration of its connections with artistic practice and the cultural field in general. We hope this approach can influence local, national and European youth education policies and enhance different approaches to research in general.